2016
DOI: 10.18632/oncotarget.13820
|View full text |Cite
|
Sign up to set email alerts
|

DPP4/CD26 overexpression in urothelial carcinoma confers an independent prognostic impact and correlates with intrinsic biological aggressiveness

Abstract: Urothelial carcinoma (UC) is common cancer worldwide. The molecular aberrations regarding tumor progression remain unclear. Pericellular proteolysis is crucial in tumorigenesis, but its significance is unexplored in UC. By data mining the datasets in Gene Expression Omnibus, specifically focus on the proteolysis pathway, and followed by a preliminary validation in a pilot batch of tumor samples, we identified that the upregulation of dipeptidyl peptidase 4 (DPP4) was most significantly associated with clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 59 publications
1
22
1
Order By: Relevance
“…sDPP4 was quantified before infection (N = 87), in primary HIV infection (PHI, N = 36), at three months post‐seroconversion (M3, N = 126) and six months post‐seroconversion (M6, N = 104). In most studies, the levels of sDDP4 are measured at the level of its enzymatic activity and absolute concentrations are more rarely presented . We measured both and as in previous studies , found a strong correlation between the concentration and enzymatic activity of sDDP4 ( R = 0.72, p < 0.0001 and Figure A).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…sDPP4 was quantified before infection (N = 87), in primary HIV infection (PHI, N = 36), at three months post‐seroconversion (M3, N = 126) and six months post‐seroconversion (M6, N = 104). In most studies, the levels of sDDP4 are measured at the level of its enzymatic activity and absolute concentrations are more rarely presented . We measured both and as in previous studies , found a strong correlation between the concentration and enzymatic activity of sDDP4 ( R = 0.72, p < 0.0001 and Figure A).…”
Section: Resultssupporting
confidence: 66%
“…multiple sclerosis, rheumatoid arthritis) and cancer (i.e. B‐cell leukaemia, hepatocellular carcinoma, bladder cancer) . In addition, DPP4 inhibitors are a widely used therapy for type II diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…It plays an important role in tumor biology by acting as a tumor suppressor or activator depending upon the level of expression and its interaction with the microenvironment and selected chemokines . In animal models, DPP4/CD26 expression has been shown to be of prognostic value and is a potential therapeutic target in various malignancies . Of note is that the first phase I clinical trial involving CD26‐expressing cancers with an anti‐CD26 monoclonal antibody was recently completed and reported prolonged disease stabilization in patients with mesothelioma with good drug tolerance …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In animal models, DPP4/CD26 expression has been shown to be of prognostic value and is a potential therapeutic target in various malignancies. [4][5][6][7] Of note is that the first phase I clinical trial involving CD26-expressing cancers with an anti-CD26 monoclonal antibody was recently completed and reported prolonged disease stabilization in patients with mesothelioma with good drug tolerance. 8 Barreira da Silva et al 9 showed that in mice models with melanoma, DPP4 inhibition preserved the active form of chemokine CXCL10 which recruits T cells in tumor parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…UDP-glucose pyrophosphorylase 2 (UDP-UGP2) encodes the enzyme important for glucose synthesis, and its expression has been found to be associated with poor outcome of a number of cancers (33,34). Dipeptidyl peptidase 4 (DPP4) functions as an ectopeptidase that can inactivate incretins, catalyze the cleavage of chemokines, promote cell migration, and activate lymphocytes; its expression is linked to the carcinogenesis of many malignant tumors (35). Calcium channel β 3 (CACNB3) was one member gene of a 4-gene prognostic model exhibiting potential clinical utility for risk stratification of stage I to stage III NSCLC patients (36).…”
Section: Discussionmentioning
confidence: 99%